Peningkatkan Kesejahteraan Mental dan Pola Hidup Sehat Lansia di Panti Werdha X - Purnomo, Hari; A.P., Rezki Amelia Aminuddin (JAST : Jurnal Aplikasi Sains dan Teknologi, 2024)
Decreased cognitive abilities and physical and motor activities are often experienced by the elderly. This research aims to explore the effectiveness of a multidimensional intervention program, which includes healthy lifestyle patterns, cognitive ergonomics training, and mental health education in improving older adults' physical and mental well-being at Nursing Home X. The research method used was a survey involving older adults as respondents. The research results showed a significant positive impact on the well-being of the elderly, namely an 80% increase in sleep quality, a reduction in stress and depression levels by 30% and 20%, respectively, an increase in cognitive abilities by 65%, and an increase in social relationships by 70%. Overall, these programs effectively improve seniors' physical and mental well-being at Nursing Home X, providing a solid foundation for improving healthcare services for seniors in the future.ABSTRAKPenurunan kemampuan kognitif, fisik dan aktivitas motorik seringkali dialami oleh lansia. Penelitian ini bertujuan untuk mengeksplorasi efektivitas program intervensi multidimensi yang mencakup pola hidup sehat, pelatihan ergonomi kognitif, dan penyuluhan kesehatan mental dalam meningkatkan kesejahteraan fisik dan mental lansia di Panti Werdha X. Metode penelitian yang digunakan adalah survei dengan melibatkan lansia sebagai responden. Hasil penelitian menunjukkan dampak positif yang signifikan bagi kesejahteraan lansia yaitu terjadi peningkatan 80% kualitas tidur, penurunan tingkat stress dan depresi masing-masing sebesar 30% dan 20%, peningkatan kemampuan koginitif sebesar 65%, dan peningkatan hubungan sosial sebesar 70%. Secara keseluruhan, program-program ini efektif dalam peningkatan kesejahteraan fisik dan mental lansia di Panti Werdha X, memberikan dasar yang kuat bagi peningkatan layanan perawatan kesehatan bagi lansia di masa mendatang.